Copper-catalyzed C-SI bond formation based on SI-B bond activation - Peng, Wang (2011)
This thesis describes copper-catalyzed carbon-silicon bond formations, including 1,4-addition to α,β-unsaturated esters, 1,2-addition to aldehydes and highly regioselective silylcupration of terminal alkynes, based on Si-B bond activation. A brief summary of traditional Si-B bond activation catalyzed by transition metal catalysts is given. Some recent examples of silylboration of terminal alkynes and unsaturated carbonyl compounds are highlighted in this chapter. The mechanisms involving Si-B bond activation of above reactions are also thoroughly discussed. A highly efficient β-silylation of α,β-unsaturated esters catalyzed by an N-heterocyclic carbene-copper complex based on Si-B bond activation has been developed. This new method produced highly functionalized products with a wide substrate scope, thus providing an ideal strategy to asymmetric transformations. A new protocol to prepare α-hydroxysilanes using an N-heterocyclic carbene copper(I) complex as catalyst has been developed and successfully applied to the addition to various aldehydes in good yields under ambient conditions. This is the first successful example to realize catalytic nucleophilic transfer of silicon to aldehydes through a Cu-Si intermediate based on Si-B bond activation.